The purge : election year [videorecording (Blu-Ray)] - Demonaco, James; Demonaco, James; Grillo, Frank, 1963-; Mitchell, Elizabeth, 1970-; Williamson, Mykelti (Universal Pictures Home Entertainment, 2018)
On the night of the annual Purge, when all crime is legal for twelve hours, a senator calling for an end to the Purge is betrayed and she finds herself and her security guard on the streets of Washington D.C. during the Purge.